2009
DOI: 10.1116/1.3123326
|View full text |Cite
|
Sign up to set email alerts
|

Improved field emission via laser processing of carbon nanotubes on paper substrates

Abstract: Field emission (FE) is the emission of electrons from a solid by the application of a high electric field via quantum mechanical tunneling of electrons through a potential barrier. Carbon nanotubes (CNTs) have excellent FE properties, 1,2,3,4 The morphology of a surface plays a crucial role in determining its FE properties. 15,16 The local field at the emission site governs FE, so micron and nanoscale protrusions can enhance FE due to increased electric field concentration at their surfaces. This enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This research had an impact on the development of a uniform and large area of FE electron sources formed in a simplified process like dip-coating, drop-casting, or filtration (Figure 5a,b) [98,[100][101][102][103], and finally screen printing (Figure 5c) [104][105][106], which is an established and well-known method for fine patterning, with increasing use for flexible electronics [107][108][109], including vacuum electronics [110,111]. The graph summarizing the techniques for the FE cathodes upon the alignment of the CNTs and the scalability is presented in Figure 6 (author's work).…”
Section: Cnt Suspension For Fe Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research had an impact on the development of a uniform and large area of FE electron sources formed in a simplified process like dip-coating, drop-casting, or filtration (Figure 5a,b) [98,[100][101][102][103], and finally screen printing (Figure 5c) [104][105][106], which is an established and well-known method for fine patterning, with increasing use for flexible electronics [107][108][109], including vacuum electronics [110,111]. The graph summarizing the techniques for the FE cathodes upon the alignment of the CNTs and the scalability is presented in Figure 6 (author's work).…”
Section: Cnt Suspension For Fe Cathodesmentioning
confidence: 99%
“…Field emission from the sidewalls of CNTs: the voltage-current (I-V) characteristic of films made of CNTs aligned parallel, at 45°, and perpendicular to the substrate (reprinted with permission from[94]). This research had an impact on the development of a uniform and large area of FE electron sources formed in a simplified process like dip-coating, drop-casting, or filtration(Figure 5a,b)[97,[99][100][101][102], and finally screen printing(Figure 5c)[103][104][105], which is an established and well-known Uniform and large area FE cathodes: (a,b) SEM images of the buckypaper surface reprinted with permission from[101] (a) and reprinted with permission from[102] (b); (c) the emission image of the screen-printed FED (reprinted with permission from[104]). …”
mentioning
confidence: 99%
“…Previous studies reported that the FE properties of CNTs [6,7] and other material such as ZnO nanowires [8] would be greatly enhanced after laser treatment. With similar structure, graphene may also have the opportunity to improve the FE properties after laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laser irradiation, post-plasma treatments, and Ar neutral beam treatments have been studied to improve the CNT field emission properties [14][15][16][17][18][19]. Of these, the laser irradiation appears to be the most accurate and rapid method to enhance the emitting performance.…”
Section: Introductionmentioning
confidence: 99%